Arsip dan Jaringan Intelektual: Studi tentang Koleksi Nishijima di Universitas Waseda Jepang - Arif Rahman Bramantya (Khazanah: Jurnal Pengembangan Kearsipan, 2017)
Archives can be said to be "inanimate" if we look it from the physical side. On the other hand, archives can be said to be "a living thing" if we look it in terms of the information that is contained in. Archives can explain anywhere, anytime and any purpose, because archives have evidential value, informational value and intrinsic value. In short, archives is a source of knowledge if we look it through academic view point. Archives in relation to the Japanese occupation in Indonesia is very limited.Nowadays, the study related to the Japanese occupation in Indonesia is also decrease. However, the study about the Japanese occupation in Indonesia in the 80s was massive and varied. Nishijima Collection is one of the valuable sources of knowledge related to the Japanese occupation in Indonesia. Unfortunately, many people do not use the collection as source for their Indonesian study. The result of this study provides a new perspective on the materials related with the Japanese occupation in Indonesia contained in Nishijima Collection. Intellectual network was formed through Nishijima Collection. Eventually, the study about Nishijima Collection through the historical method can be an initial foundation to raise the historical awareness that will be able to affect the civilization (of Indonesia).